The Appropriation of Symbolic Language in Worldview Education through Bibliodrama - Bas van den Berg; Cocky Fortuin-van der Spek (MDPI AG, 2019)
One of the main questions regarding Dutch primary education in our secularised and religiously diverse society—both with regards to public and religiously-affiliated schools—is how to get students acquainted with the symbolic language of religious and worldview-affiliated life narratives. Teaching literacy in symbolic language has become less important in the education programmes of modern-day primary schools. The dominance of scientific descriptive language is evident in the majority of contemporary curricula. This language may be highly important for teaching mathematics and science, but for religious and cultural education, and for teaching art and history, symbolic language is the vehicle for acquiring knowledge, insight, and wisdom. Our aim in this article is to reflect on the idea that stimulating symbolic speech in primary school education through role playing, will bring out the sensitivity of current-day students to confer meaning to life questions and life themes.